The Relationship Between Pattern Making and Pattern Alteration Skills and Students’ Learning Outcomes in Tailoring - Nila Roudlotul Jannah; Irmayanti Irmayanti (Universitas Negeri Semarang, 2026)
Basic pattern making and pattern alteration skills are essential competencies that must be mastered by students in the Tailoring course. These skills serve as the foundation in the tailoring garment production process, which requires accuracy in measurements, proportions, and pattern construction. This study aims to determine the relationship between the level of basic pattern making and pattern alteration skills and students’ learning outcomes in the Tailoring course. This research employed a quantitative approach with a correlational method. The research subjects were students of the Fashion Education Study Program who were enrolled in the Tailoring course. Data on basic pattern making and pattern alteration skills, as well as tailoring course scores, were obtained from students’ academic records. Data analysis was conducted using correlation analysis. The results of the study indicate that there is a positive and significant relationship between the level of basic pattern making and pattern alteration skills and students’ learning outcomes in the Tailoring course. This finding suggests that the higher the students’ skills in basic pattern making and pattern alteration, the better the learning outcomes achieved. Therefore, basic pattern making and pattern alteration skills need to receive greater attention and reinforcement in the Tailoring learning process to improve students’ learning outcomes